Strategies for Increasing Young Family Engagement in Couple Ministry Programs at GKII Rehobot Mustikajaya Bekasi - Jawakory, Patricia Ina; Wijiati, Wahyu (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2026)
This study aims to analyze strategies for increasing young family engagement in the Couple Ministry Commission programs at GKII Rehobot Mustikajaya Bekasi. Employing a qualitative approach and a case study design, the research explores the experiences, perceptions, and contextual challenges faced by young families within an urban and digitalized environment. Data were collected through in-depth interviews, observations, and document analysis and were subsequently analyzed using thematic analysis. The findings reveal that low levels of engagement are influenced by work-related pressures, limited family time, urban mobility, digital distractions, and a ministry model that is predominantly activity-oriented and lacks relational depth. The study highlights the importance of developing ministry approaches that are relational, contextual, and discipleship-oriented through small-group communities, flexible ministry models, digital support systems, and family empowerment initiatives.